2018
DOI: 10.1364/boe.9.000543
|View full text |Cite|
|
Sign up to set email alerts
|

Methods for detecting host genetic modifiers of tumor vascular function using dynamic near-infrared fluorescence imaging

Abstract: Vascular supply is a critical component of the tumor microenvironment (TME) and is essential for tumor growth and metastasis, yet the endogenous genetic modifiers that impact vascular function in the TME are largely unknown. To identify the host TME modifiers of tumor vascular function, we combined a novel genetic mapping strategy [Consomic Xenograft Model] with near-infrared (NIR) fluorescence imaging and multiparametric analysis of pharmacokinetic modeling. To detect vascular flow, an intensified cooled came… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…We previously reported that the inbred Dahl saltsensitive/Mcwi (SS) rat strain was more sensitive to localized image-guided cardiac radiation than the Brown Norway (BN) strain, and that substitution of chromosome 3 from the BN strain into the SS background (SS.BN3 consomic rats) confers dramatic resistance to radiation-induced cardiac dysfunction when compared to the SS strain (22). Consomic chromosome substitution studies can be used to map complex genetic modifiers of pathophysiologic phenotypes (23)(24)(25)(26). In our previous consomic rat study with the SS strain that was relatively sensitive to localized cardiac radiation when compared to the SS.BN3 consomic strain, the top genetic pathways differentially expressed between SS and SS.BN3 consomic rat ventricles 1 week after radiation included mitochondrial-related genes (22).…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that the inbred Dahl saltsensitive/Mcwi (SS) rat strain was more sensitive to localized image-guided cardiac radiation than the Brown Norway (BN) strain, and that substitution of chromosome 3 from the BN strain into the SS background (SS.BN3 consomic rats) confers dramatic resistance to radiation-induced cardiac dysfunction when compared to the SS strain (22). Consomic chromosome substitution studies can be used to map complex genetic modifiers of pathophysiologic phenotypes (23)(24)(25)(26). In our previous consomic rat study with the SS strain that was relatively sensitive to localized cardiac radiation when compared to the SS.BN3 consomic strain, the top genetic pathways differentially expressed between SS and SS.BN3 consomic rat ventricles 1 week after radiation included mitochondrial-related genes (22).…”
Section: Introductionmentioning
confidence: 99%
“…Optical imaging in near-infrared (NIR) wavelength range is a non-invasive imaging that can sensitively track biochemical events using fluorescent dyes and nanomaterials. Cy5.5 dye loaded L-NIR-Fe 3 O 4 /OX phantoms or anesthetized rats were imaged by near-infrared (NIR) fluorescence imaging system (Ī» ex /Ī» em =663nm/longpass 700nm) at 100 ms exposure time using the method described elsewhere 26 . A 663 nm diode laser (90 mW) with deep cooled intensified charge-coupled device (ICCD) camera (PiMAX, Princeton Instruments, Trenton, NJ) was used for fluorescence imaging.…”
Section: Methodsmentioning
confidence: 99%
“…A homologous mechanism has been replicated in human T lymphocytes [41] and associated with human breast cancer risk [42]. In another example, a newly developed genetic mapping strategy, Consomic/Congenic Xenograft Model (CXM), was used to identify a host TME modifier locus that is linked with DLL4 and impacts breast cancer growth and metastasis in the rat by inducing dysfunctional angiogenesis, which was independent of tumor cell changes [43ā€“45]. Further evidence of host TME modifiers exist in mouse genetic mapping studies, including three modifier loci (Mmtg1-3) that were linked with mammary tumor angiogenesis [46] and PTPRJ, a mediator of angiogenesis [47] that was originally discovered for its role in susceptibility to colon cancer, and has since been linked with breast cancer risk [48].…”
Section: Intersection Of Breast Cancer Heritability and The Tumor Micmentioning
confidence: 99%
“…The capacity of this approach could be expanded using high density tissue microarrays and quantitative immunofluorescent imaging, which offers highly sensitive and spatially resolved detection of protein expression at the cellular and subcellular levels [84ā€“87]. Finally, we recently developed CXM as the first experimental strategy for genetic mapping of host TME modifiers [43ā€“45]. In CXM, human breast cancer cells or patient-derived xenografts (PDX) are orthotopically implanted into genetically-engineered consomic or congenic xenograft host strains (mice or rats), which are derived from two parental strains with different susceptibilities to breast cancer.…”
Section: Challenges To Identifying Host Tme Modifiers Of Breast Cancermentioning
confidence: 99%